Family members' or friends' involvement in self-care for patients with depressive symptoms and co-morbid chronic conditions. (September 2016) - Sussman, Tamara; Mccusker, Jane; Yaffe, Mark; Belzile, Eric; Sewitch, Maida; Cole, Martin; Strumpf, Erin
Objectives: To describe the support that patients reported receiving from family or friends (F/F) while participating in a self-care intervention for depressive symptoms; examine associations between patient-reported F/F support and use of self-care materials; and describe F/F perceptions of involvement in a subsample of F/F. Methods: One hundred eighty-nine of 223 (85%) patients aged 40+ with chronic physical conditions and co-morbid depressive symptoms participating in a randomized self-care intervention trial, completed structured telephone surveys at three months about the F/F support received. Ten F/F participated in post study qualitative interviews on the support provided. Results: 30%, 44%, and 91% of patients reported overall F/F support with self-care, F/F involvement with the self-care intervention and emotional support, respectively. 61% felt positively and 10% felt negatively or conflicted with F/F support. F/F involvement in the self-care intervention was the only variable associated with patient use of self-care materials when examined alongside all F/F support variables (Proportional Odds Ratio = 1.21; 95% C.I. = 1.01, 1.45). F/F perceived less involvement in the self-care intervention than patients. Discussion: Patients engaged in a self-care intervention for depressive symptoms use more self-care materials when they perceive F/F involvement in the intervention. Patients and F/F may perceive involvement differently and benefit from discussions about potential F/F roles.